An actual problem in the production of ceramic tiles - Kaliyeva, Жанар; Ospan, Нұргүл (Рroblems of engineering and professional education, 2023)
The article discusses the analysis of the state of production of ceramic tiles in the whole country and in the regions. It is revealed that one of the urgent problems of the industry of ceramic tiles is providing the production with high quality raw materials.